Variation of WC grain shape with carbon content in the WC-Co alloys during liquid-phase sintering - Kim, S; Han, SH; Park, JK; Kim, HE (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
WC-Co hard metals have faceted WC grains dispersed in a ductile cobalt-rich matrix. The effect of carbon (C) content on the shape of WC grain in the WC-Co metals during liquid-phase sintering is investigated in this work. The WC grain shape varies with the C content and, more importantly, the shape change occurs reversibly with the C content. (C) 2002 Acta Materialia Inc. Published by Elsevier Science Ltd. All rights reserved.
Keywords: CEMENTED CARBIDES